40 years of slavery studies - Engerman, Stanley (História Econômica & História de Empresas, 2015)
In this lecture, read at the 7th Graduate Meeting of Economic History, held at Universidade Federal Fluminense, in 2014, Stanley Engerman examines 30 topics concerning academic studies about the social institution of slavery. He analysis since the first studies, which emphasized moral aspects of the compulsory and the free labor in Modern world, to studies of the working of slave systems in the Americas, as well as he dedicates special attention to the recent developments in this field of the historical knowledge. About this last topic, Engerman delves into the economic and demographic implications of the slave systems, seen in comparative perspective.